Morphological characteristics and phylogenetic analyses revealed Gyrophanopsis changlinii sp. nov. (Polyporales, Basidiomycota) from Southwest China - Xiao, Wenyuan; Li, Yunchao; Gu, Zirui; Zhou, Hongmin (Phytotaxa, 2025)
A new species, Gyrophanopsis changlinii is described and illustrated based on morphological and molecular evidence. This species is characterized by its white resupinate araneose basidiomata and cylindrical basidiospores (4.5–5.3 × 4.1–4.9 µm). Sequences of the internal transcribed spacer region (ITS) and the large subunit nuclear ribosomal RNA gene (nLSU) from the studied samples were generated, and phylogenetic analyses were performed using Maximum Likelihood, Bayesian Inference, and Maximum Parsimony methods. The phylogenetic analyses indicated that the new species, G. changlinii nested within the genus Gyrophanopsis, sister to three related species: G. japonica, G. polonensis, and G. zealandica.